The response of sectoral returns to macroeconomic shocks in the Malaysian stock market - Law, Siong Hook; Ibrahim, Mansor (Faculty of Economics & Administration, University of Malaya and Malaysian Economic Association, 2014)
This paper examines the responses of sectoral returns to shocks in five macroeconomic indicators using the vector autoregressive (VAR) model and generalised impulse response functions for an emerging stock market, Malaysia. The empirical results suggest that, while the temporal responses of sectoral returns to macroeconomic shocks are relatively identical, their initial responses are slightly different. Monetary policy and exchange rate shocks have the largest effect on the finance sector, whereas output and exchange rate shocks exert most influence on the property sector. Comparatively, among the shocks, monetary shocks (i.e., money supply, interest rate and exchange rate shocks) are more influential in influencing sectoral returns than goods market shocks (i.e., output and consumer price shocks).